Sustainable procurement disclosure practices in central public sector enterprises: Evidence from India. Issue 2 (June 2015) - Mansi, Mansi
Abstract The objective of this study is to explore sustainable procurement practices across Central Public Sector Enterprises (CPSE) in India, and particularly to understand how CPSEs operationalise and disclose sustainable procurement (SP) practices. This study uses a content analysis methodology to review the SP disclosure practices of top 50 CPSEs selected on the basis of annual turnover. Out of the eight SP dimensions examined in this study, it is interesting to note that the maximum disclosures were under economic development, philanthropy and community development practices. This study finds that 'product responsibility' reporting is minimal in quantity and is not combined with other elements of sustainable procurement. The study developed a strong and robust SP disclosure index (SPDI) comprising the eight dimensions of sustainable procurement. This study breaks new ground and provides a springboard for future research to investigate SP practices in India and other developing countries. This study provides several important implications and is an original contribution to the literature.